The mess inside narrative, emotion, and the mind - Goldie, Peter (Oxford : Oxford University Press, 2012)
Peter Goldie explores the ways in which we think about our lives in narrative terms. He draws on work in philosophy, psychology history, and literature, and argues that having a narrative sense of self is at the heart of what it is to understand ourselves.
Description based on online resource; title from home page (viewed on July 13, 2012).
Includes bibliographical references and index.
Keywords: Philosophy of mind; Self-consciousness (Awareness)